2019
DOI: 10.1007/s40263-019-00633-3
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Statin Use and Depressive Symptoms in a Large Community-Dwelling Older Population Living in Australia and the USA: A Cross-Sectional Study

Abstract: All authors actively participated in designing the current study. BA and MM performed the data analysis. BA drafted the manuscript that has been read, edited and approved by all co-authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
8
1
Order By: Relevance
“…The remaining studies involved elderly participants. Outcomes based on a Geriatric Depression Scale (GDS) or a Centre for Epidemiologic Studies – Depression (CES-D) score above threshold for diagnosis of depression were reported in three studies with conflicting results: one showed a decreased prevalence of depression in statin users ( N = 2,804, OR = 0.71, 95% CI = 0.52–0.97) ( 101 ), another reported no difference in prevalence among South Asian and African-Caribbean statin users ( N = 695, OR = 1.67, 95% CI = 0.97–2.88) nor White Europeans ( N = 638, OR = 0.54, 95% CI = 0.26–1.13) ( 103 ) though a significant ethnicity-statin interaction ( P = 0.041), while a further study in 19,114 elderly community-dwelling participants found no association (OR = 1.09, 95% CI = 0.98–1.20) ( 99 ).…”
Section: Resultsmentioning
confidence: 95%
“…The remaining studies involved elderly participants. Outcomes based on a Geriatric Depression Scale (GDS) or a Centre for Epidemiologic Studies – Depression (CES-D) score above threshold for diagnosis of depression were reported in three studies with conflicting results: one showed a decreased prevalence of depression in statin users ( N = 2,804, OR = 0.71, 95% CI = 0.52–0.97) ( 101 ), another reported no difference in prevalence among South Asian and African-Caribbean statin users ( N = 695, OR = 1.67, 95% CI = 0.97–2.88) nor White Europeans ( N = 638, OR = 0.54, 95% CI = 0.26–1.13) ( 103 ) though a significant ethnicity-statin interaction ( P = 0.041), while a further study in 19,114 elderly community-dwelling participants found no association (OR = 1.09, 95% CI = 0.98–1.20) ( 99 ).…”
Section: Resultsmentioning
confidence: 95%
“…Presence of probable depression (CES-D-10 score ≥ 10) and probable anxiety (GAD-7 score ≥ 5) were used as dependent variables. In line with many published studies, we dichotomized scores of the CES-D-10 and GAD-7 and used logistic regression models to investigate factors associated with probable depression and probable anxiety [46][47][48]. Two-level logistic regression models (level 1: towns/communities, level 2: individual older PLWH) were fit to analyze factors associated with the dependent variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In the study of Alghamdi et al [14], the depression rate was increased in patients who used statin and PCSK9 inhibitor treatment. Agustini et al [15] followed patients using statins in terms of depression and concluded that the issue should be managed pharmaco-epidemiologically due to the increased depression rate. In a Danish study conducted with 193,977 statin users by Ole Köhler-Forsberg et al [16], the relationship between the agent and depression was unclear and statin use was not a risk factor.…”
Section: Discussionmentioning
confidence: 99%